196k views
1 vote
3 (2x+1) -4 = 2x+3 it this a no solution, one solution, or a one solution if 1 of the 2 please tell me what is x to

2 Answers

2 votes

Answer:

One Solution, X is equal to 1.

Explanation:

3(2x+1) -4 = 2x + 3

distribute

6x+3 -4 = 2x + 3

-3. -3

(+3 on both sides mean they will cancel out)

6x -4 = 2x

-2x. -2x

4x = 4

x is 1.

you can test if this is true by reinserting 1 into x on both sides.

3(2(1)+1) -4 = 2(1) +3

3(3) -4 = 2+3

9-4 = 2+3

5=5

User Brig Ader
by
5.8k points
6 votes

Answer:

No Solution

Explanation:

User Nosuic
by
7.2k points